Atomic Marginal Distribution and Squeezing Phenomena of Correlated Two Modes Interacting with a Three-Level Atom in the Presence of an External Classical Field - A.-S. F. Obada; E.M. Khalil; S. Sanad; H.F. Habeba (International Journal of Optics)
The influence of the external classical field on a correlated two-mode of the electromagnetic field interacting with a three-level atom in the Λ structure is studied. A rotation of the atomic basis is used to remove the classical field terms. The time-dependent wave function is obtained by solving the Schrödinger equation. The influence of the classical field on the phenomenon of revival, collapse, squeezing, and marginal atomic distribution are discussed. In our analysis, the cavity field is prepared in the entangled pair coherent states and the atomic system in the upper state. The results showed that the occupation of the atomic level is significantly affected by the addition of the classical field. The presence of the classical field reduces the squeezing intervals and the extreme values of the atomic marginal distribution.